Epinephelus sicanus (Doderlein, 1882) (Perciformes: Serranidae: Epinephelinae), a valid species of grouper from the Mediterranean Sea - Bellia, Enrico; Cerasa, Giuliano; Cigna, Vincenzo; Brutto, Sabrina Lo; Massa, Bruno (Zootaxa, 2020)
During the editing of the paper “In memory of Pietro Doderlein” (Massa et al. 2018), consulting Doderlein’s bibliography, and highlighting some interesting documents and the material preserved in the Museum of Zoology of the University of Palermo (MZPA) (today named after Doderlein), a taxonomic anomaly was noticed about a grouper collected more than one hundred years ago. The aim of the present statement is to prove that the name Cerna sicana Doderlein, 1882 (presently as Epinephelus sicanus [Doderlein, 1882]) should be considered a valid species unless it is demonstrated that it is a synonym of another valid species. In 1882 Doderlein described Cerna sicana from a single specimen (Fig. 1). The holotype is a female, composed of three parts: MZPA-P/46 comprising the stuffed specimen bearing the external anatomical features (Fig. 1), MZPA-AN/440 comprising the dry gill arches and the heart (Fig. 2), and MZPA-AN/1233 comprising the vertebral column (Fig. 3). The eyes and the digestive and reproductive organs, originally stored in liquid, are lost. The specimen was collected in the central Mediterranean Sea along the coast of northern Sicily (Palermo), southern Italy, in December 1882 and deposited at the Museum of Zoology “P. Doderlein” of the University of Palermo. Later Doderlein (1889) moved the species to the genus Epinephelus Bloch, 1793. About his new species, Doderlein (1882) wrote (translated from Italian): “Serranus Cernioides, Brito Capello, and Serranus Caninus, Val., are those most related to this … It should be established if its characters could allow it to be described as a new species or if they could be anomalies of one of the previously cited species. In order to highlight the peculiar characters, I tentatively decide to name it Serranus or Cerna Sicana, after the locality where it was caught”. Doderlein (1889) wrote about the new species to D.S. Jordan[1] then at the Indiana University of Bloomington (USA), who replied that he considered E. sicanus as a valid species, and that Jordan noted two other adults and a third young specimen collected in Brazil, in 1865, in the Louis Agassiz collection, preserved in the Museum of Cambridge (presently Museum of Comparative Zoology—MCZ, Harvard University, USA) that he considered as possibly conspecific with E. sicanus. According to A. Williston (MCZ curator, pers. comm.) two likely candidates for these Jordan-Doderlein specimens are still present in the museum (voucher codes MCZ 9787 and MCZ 9788), identified as “Epinephelus (allied to nigritus, perhaps new)”. Soon after, Jordan & Eigenmann (1890) synonymized Cerna sicana with Epinephelus merus (Poey, 1868). Subsequently, Boulenger (1895) synonymized Epinephelus merus and E. sicanus with Epinephelus nigritus (Holbrook, 1855), apparently without observing the holotype of C. sicana as argued by Tortonese (1956). [1]       Jordan (1891) described Symphodus doderleini with the following etymology: “We have given to it the new name of Symphodus doderleini, in honor of our excellent friend Prof. Pietro Doderlein of the University of Palermo”; this is a proof of the esteem that he had for him.